Synthetic Studies toward Tubiferal A: Asymmetric Synthesis of a Model ABC-Ring Compound - Yukutake, Yuki; Hiramatsu, Takahiro; Itoh, Ryusei; Ikeuchi, Kazutada; Suzuki, Takahiro; Tanino, Keiji (Synlett, 2021)
Synthetic studies on an ABC-ring model of tubiferal A, a triterpenoid isolated from the fruit bodies of the Tubifera dimorphotheca myxomycete, are described. The stereogenic centers at the angular positions were constructed through the stereoselective addition of a C-ring allylborane followed by an Eschenmoser–Claisen rearrangement reaction prior to the formation of the AB-ring system by a double intramolecular alkylation reaction of a dichloro nitrile intermediate.
Keywords: cyclization reactions; allylboranes; nitriles; epoxides; natural products